An Inquiry on the Social and Education Status of Women from Northern Cameroon Suffering Cervical Cancer and the State of Knowledge of their Disease (Journal of Analytical Oncology, 2021)
Background: Cervical cancer is a major cause of women death worldwide. The reduction of the mortality and morbidity of this pathology depends on the early detection based on powerful suitable screening methods, that will lead to optimal treatment strategies. However in some rural region of developing countries, it is very difficult to get access to standard screening methods, alternative screening methods, cheaper and easy to handle are then useful.Objective: The aim of this work was to test the sensitivity and specificity of VIA (Visual inspection with acetic acid) and VILI (Visual inspection with lugol iodine) as screening test of cervical cancer compared to the Pap Smear, evaluating the feasibility in health formation in the North Cameroon region, of implementing epidemiological surveillance of cervical cancer based on early diagnosis using the VIA-VILI associationMethod: 309 women age 20 to 62 years were recruited in this study, 307 were included in the statistical analyzes. Each woman was screened for cervical cancer by a conventional Smear and visual inspection with acetic acid 5% and the lugol solution.Results: We found in our study a prevalence of precancerous lesions of cervix at 12.70%. The risks factors of cervical cancer identified are age, matrimonial status, age of first sexual intercourse and parity. The association of VIA and VILI showed a sensitivity, specificity, positive and negative predictive value respectively about 93.58%; 97.01%; 82.01%, 99.04%.Conclusion: Compared to PAP Smear, VIA or VILI could be used as an alternative screening methods for cervical cancer in developing countries. However, histology test was recommended to use a « Gold Standard » to evaluate the test accuracy of VIA/VILI because it can be used to diagnose cancer, while PAP smear cannot.